YAP1 Rearrangement in Parotid Sclerosing Mucoepidermoid Carcinoma - Sherif Y. El-Nagdy; Pushparaja Shetty; Bacem Abdullah; Shahram Sabeti (Journal of the California Dental Association, 2024)
Objective This study investigates to investigate Yes-associated protein 1 (YAP1) rearrangement status in a six-case of sclerosing mucoepidermoid carcinoma (SMEC) series with reference to 20 conventional mucoepidermoid carcinomas.Method A retrospective analysis was conducted on a cohort of patients diagnosed with SMEC from 2018 to 2022. The presence of YAP1 rearrangement was determined using fluorescence in situ hybridization (FISH) analysis targeting the YAP1 gene located at 11q22.1-q22.2. Clinical data, including patient outcomes, were collected and analyzed. Next-generation sequencing (NGS) was performed to identify the fusion partner involved in the YAP1 rearrangement.Results A total of six cases of SMEC were included in the study, of YAP1::MAML2 fusion was detected and five cases showed YAP1 rearrangement on FISH testing.Conclusion YAP1 alteration may explain the indolent nature of SMECs, especially in cases with low cellularity. Further studies incorporating NGS analysis are warranted to unravel the fusion partner associated with YAP1 rearrangement, providing a deeper understanding of the molecular mechanisms underlying the positive outcomes observed in these patients.